Prediction Model and Scoring System in Prevention and Control of Stunting Problems in Under Five-Year-Olds in Indonesia (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Prevalence of stunting in Indonesia is a cause for concern. We used IFLS 2007 as secondary data in the cross-sectional study to develop a problem-solving and prevention model of stunting. The study was conducted in 2016 to predict a model from the characteristics, parents, and health care of the child. We recruited 3589 children under-five years from IFLS 2007 data as samples. The inclusion criteria are 1-5 years old children from 15-49 years old pregnant women, living with biological parents, available data of birth weight and gestational age, and do not have chronic disease. We used multiple logistic regression for modeling, and Receiver Operation Characteristic (ROC) Curve as a diagnostic test. We found that 39.5% of children under-five have stunting. Stunting protective factors are: prevention of LBW (Low Birth Weight) in infant, limitation of number of children by three, improved parenting for the boys, prevention of young-age pregnancy and stunting in the female adolescent. Other factors are completing immunization, improving maternal education and the health services of under-five children in rural areas, and improving Fe consumption for pregnant mothers. The model was able to prevent and delay the stunting in toddler by 64%, with 61.9% sensitivity and 60.9% specificity, and AUROC 65.5%. It is necessary to counsel the pregnant women with a low height and young-age pregnancy as a high risk, as well as management of the infant with LBW to prevent stunting.